Peripheral nerve and muscle disease - Cohen, Jeffrey A. (Jeffrey Allen), 1951- (What do I do now?, 2009)
This book is a case-based learning guide for neuromuscular diseases. This second volume in the What Do I Do Now? series, Peripheral Nerve and Muscle Disease recreates real clinical situations in which the attending is asked for advice as the neurological consultant. The approach to the clinical question is discussed emphasizing differential diagnosis and treatment pathways. The authors have included clinical pitfalls which they have experienced in their own practice. This is a readable book which can be picked up in spare moments.